Design And Evaluation Of Teneligliptin Tablet: Teneligliptin Tablet - Ritu Chauhan; Anuradha Verma; Tushar Singhal; Anshika Garg; Babita Kumar; Dayanidhi Pandey (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2023)
Background : Excessive workload, stress, and, genetic disorders are the main reason for the increasing prevalence of Type II diabetes in India. Teneligliptin, is a potent Dipeptidyl peptidase (DPP-4) inhibitor that exerts its action in Type II diabetes mellitus. Teneligliptin mainly acts by increasing insulin levels and decreasing glucagon levels in the circulation in a glucose-dependent manner. It offers sufficient glycemic control in a period of 12 weeks ad is also tolerable by renal-impaired patients. Methods: Six formulations of teneligliptin tablets were prepared by using different ratios of MCC, maize starch, HPMC, HPC, aerosol, and magnesium stearate. The prepared tablets were evaluated in terms of friability, hardness, disintegration, and dissolution rate profile Results: Out of all six formulations, F4 reflects better tablet characteristics as compared to the rest five formulations Conclusions: F4 turns out to be the best formulation of the present study and can be used for commercial production.